Recent Updates on Computer-aided Drug Discovery: Time for a Paradigm Shift - Usha, Talambedu; Shanmugarajan, Dhivya; Goyal, Arvind K.; Kumar, Chinaga Suresh; Middha, Sushil Kumar (Current Topics in Medicinal Chemistry, 2017)
Computer-Aided Drug Designing (CADD) has gained a wide popularity among biologists and chemists as a part of interdisciplinary drug discovery approach. It plays a vital role in the discovery, design and analysis of drugs in pharmaceutical industry. It is extensively used to reduce cost, time and speed up the early stage development of biologically new active molecules. In the current review we presented a brief review of CADD, merits and demerits, DNA, protein and enzyme as targets, types of CADD: Structure Based Drug Designing (SBDD), Ligand Based Drug Designing (LBDD), Pharmacophore based drug designing (PBDD) and Fragment Based Drug Designing (FBDD), theory behind the types of CADD and their applications. The review also focuses on the in-silico pharmokinetic, pharmacodynamic and toxicity filters or predictions that play a major role in identifying the drug like molecules. Currently in pharmaceutical sciences computational tools and software are exhibiting imperative role in the different stages of drug discovery hence the review throws light on various commercial and freeware available for each step of CADD.
Keywords: Drug discovery